Analisis Efektivitas dan Kontribusi Penerimaan Pajak Bumi dan Bangunan (PBB) terhadap Pendapatan Asli Daerah di Kota Medan: Study Kasus Kantor Dispenda Medan - Oktianty, Indah; Hastuty, Widy (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This study aims to : (1) Analyze Land and Building Tax (PBB) revenues in accordance with the targets set during 2017 to 2021 ; (2) Determine the contribution of Land and Building Tax (PBB) revenues to Regional Original Income (PAD) in the Medan City government from 2017 to 2021 ; (3) Analyze the factors that led to a decrease in the number of Tax Returns Payable (SPPT) in paying Bunt and Building Tax (PBB) in 2017 to with 2021. In this study the authors took a descriptive approach, the data source used primary data. The data analysis technique used in this study used the effevtiveness ratio and contribution formula. The result of this study advanced that (1) Realization of Land and Building Tax (PBB) revenues in general reched the target set with the average revenue effectiveness categorized as quite effective (2) The contribution of Land and Building Tax (PBB) to Regional Original Income (PAD) has agretes value compared to other regional taxes with an average contribution categorized as moderate (3) Factors that influence the reduction of Tax Returns Payable (SPPT) in paying taxes caused by internal factors and external factors